Integrated Organic Binder from Local Materials of Uzbekistan - A.M. , Karabaev (International Journal of Psychosocial Rehabilitation, 2020)
Integrated organic binders created in Uzbekistan and the CIS countries are considered. The composition and properties of the constituent components of integrated organic binders (IOB) were studied. The composition of the integrated organic binders was optimized by the method of mathematical planning of experiments. A model of viscosity of IOB with the content of not enough and defecate is obtained